2014
DOI: 10.4196/kjpp.2014.18.5.411
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Remodelling in Chronic Nicotine-Administered Rat

Abstract: Vascular remodelling is an adaptive mechanism, which counteracts pressure changes in blood circulation. Nicotine content in cigarette increases the risk of hypertension. The exact relationship between nicotine and vascular remodelling still remain unknown. Current study was aimed to determine the effect of clinically relevant dosage of nicotine (equivalent to light smoker) on aortic reactivity, oxidative stress markers and histomorphological changes. Twelve age-matched male Sprague-Dawley rats were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Reactivity towards vasoconstrictor agonist, PE, and endothelium-dependent vasorelaxant agonist, ACh, determines sensitivity of the aorta [11]. Hypertension causes relatively high aorta contractility but low aorta relaxation in response to PE and ACh, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactivity towards vasoconstrictor agonist, PE, and endothelium-dependent vasorelaxant agonist, ACh, determines sensitivity of the aorta [11]. Hypertension causes relatively high aorta contractility but low aorta relaxation in response to PE and ACh, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Structural remodeling is often coupled with impaired vascular reactivity. This phenomenon was clearly demonstrated in rats undergoing chronic nicotine administration [11]. One of the key factors that results in hypertensive vessels and impaired vascular reactivity is low bioavailability of nitric oxide (NO) [12].…”
Section: Introductionmentioning
confidence: 99%
“…This supports the theory that nicotine may chronically alter aortic distensibility. Indeed, in vitro models have shown that nicotine alone has aortic-remodeling properties and may alter smooth muscle cells from contractile to synthetic type [184,185].…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…Prolonged exposure to nicotine via cigarette smoking, chewable tobacco, as well as nicotine inhalation devices is associated with an increased risk of cardiovascular diseases (McEvoy et al, 2015;Kim et al, 2017;Kunutsor et al, 2018). In animal models, prolonged administration of nicotine not only promotes vascular endothelial dysfunction associated with hypertension, but also directly impacts the cardiac structure and function, promoting oxidative stress, inflammation, fibrosis, and cardiomyocyte apoptosis (Joukar et al, 2012;Zainalabidin et al, 2014;Ramalingam et al, 2016;Si et al, 2017a;Li et al, 2018). In several lines of evidence, nicotine was shown to induce cardiac damage independent of hypertension, directly accounting for significant reduction in cardiac function (Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%